Risk of overusing mobile phones: Technostress effect - Veera Boonjing; Pisit Chanvarasuth (My University, 2017)
Technostress is defined as the stress derived from the use of information technology. Prior researchers have studied this phenomenon in many situations such as in the work environment, concentrating on the effect of technostress on the individual who overwhelmed by the use of information technology on his/her job. In this study, we attempt to examine consequences of continuously overusing mobile phone which lead to technostress. Drawing from the stress-strain-outcome model of stress, we proposed that overusing mobile phone can lead to technostress, whereas technostress will cause problems in personal health and work-related issues. Results from surveying 400 working professionals provide a support for our proposed model.
Keywords: Technostress; Mobile phone; Technostress in Professional Settings